Adjunctive IgM-enriched immunoglobulin therapy with a personalised dose based on serum IgM-titres versus standard dose in the treatment of septic shock: a randomised controlled trial (IgM-fat trial). Issue 2 (11th February 2021) - Biagioni, Emanuela; Tosi, Martina; Berlot, Giorgio; Castiglione, Giacomo; Corona, Alberto; De Cristofaro, Maria Giovanna; Donati, Abele; Feltracco, Paolo; Forfori, Francesco; Fragranza, Fiorentino; Murino, Patrizia; Piazza, Ornella; et al.
Abstract : Introduction: In patients with septic shock, low levels of circulating immunoglobulins are common and their kinetics appear to be related to clinical outcome. The pivotal role of immunoglobulins in the host immune response to infection suggests that additional therapy with polyclonal intravenous immunoglobulins may be a promising option in patients with septic shock. Immunoglobulin preparations enriched with the IgM component have largely been used in sepsis, mostly at standard dosages (250 mg/kg per day), regardless of clinical severity and without any dose adjustment based on immunoglobulin serum titres or other biomarkers. We hypothesised that a personalised dose of IgM enriched preparation based on patient IgM titres and aimed to achieve a specific threshold of IgM titre is more effective in decreasing mortality than a standard dose. Methods and analysis: The study is designed as a multicentre, interventional, randomised, single-blinded, prospective, investigator sponsored, two-armed study. Patients with septic shock and IgM titres <60 mg/dL will be randomly assigned to an IgM titre-based treatment or a standard treatment group in a ratio of 1:1. The study will involve 12 Italian intensive care units and 356 patients will be enrolled. Patients assigned to the IgM titre-based treatment will receive a personalised daily dose based on an IgM serum titre aimed at achieving serum titres above 100 mg/dL up to discontinuation of vasoactive drugs or day 7 after enrolment. Patients assigned to the IgM standard treatment group will receive IgM enriched preparation daily for three consecutive days at the standard dose of 250 mg/kg. The primary endpoint will be all-cause mortality at 28 days. Ethics and dissemination: The study protocol was approved by the ethics committees of the coordinating centre (Comitato Etico dell'Area Vasta Emilia Nord) and collaborating centres. The results of the trial will be published within 12 months from the end of the study and the steering committee has the right to present them at public symposia and conferences. Trial registration details: The trial protocol and information documents have received a favourable opinion from the Area Vasta Emilia Nord Ethical Committee on 12 September 2019. The trial protocol has been registered on EudraCT (2018-001613-33) on 18 April 2018 and on ClinicalTrials.gov (NCT04182737 ) on 2 December 2019.